E-money Analysis Of Debt Receivables Based on Sharia Perspective - Tapi Rumondang Sari Siregar; Tuti Anggraini; Asmuni Asmuni (Institut Agama Islam Negeri Padngsidimpuan, 2022)
The development of receivable transactions is currently increasingly complex. E-money is a transaction related to receivables or deposits. Every transaction that gives rise to receivables should be recorded (mahkum fiih) by the transacting party (mahkum alaih). This command is contained in the letter Al-Baqarah verse 282, this verse is the legal basis for recording. Transactions in e-money are always recorded by the issuer. The lawful use of electronic money creates differences of opinion. The Indonesian Ulema Council issued a fatwa allowing the use of Islamic electronic money as long as it did not violate the stipulated provisions. Some scholars believe that giving discounts (discounts) in e-money is haram because it provides benefits or advantages, and any credit that provides benefits or advantages for creditors is usury. This type of research is a literature study by collecting documentation from articles, journals, books, or other sources. The data processing and analysis technique in this research is descriptive analysis.